Gamification in ELT: A Systematic Review of Its Effects on Learner Engagement and Motivation - Ammang Latifa; Dzul Ashfiah; Rafi’ah Nur; Salasiah Ammade; Syawal (Faculty of Education and Teacher Training of UIN Palopo, 2025)
Gamification is gaining increasing attention in English Language Teaching (ELT) as a strategy to increase learner engagement and motivation through game elements such as points, badges, leaderboards, and digital platforms such as Kahoot, Duolingo, and Quizizz. This Systematic Literature Review (SLR) analyzes 30 empirical studies published between 2021 and 2025 using the PRISMA framework to investigate the effects of gamification on learner motivation and engagement. The review finds that gamification generally has a positive impact on learner participation and enjoyment, increasing intrinsic and extrinsic motivation. However, challenges remain regarding the long-term sustainability of these motivational benefits and the risks of over-reliance on extrinsic rewards. The analysis also reveals that while digital tools dominate gamification in ELT, the use of mixed or adaptive strategies is limited. Furthermore, little research addresses the long-term effects of gamification on language proficiency and skill retention. These findings highlight the need for future research to explore adaptive gamification models, the integration of non-digital elements, and their alignment with pedagogical principles. This review offers valuable insights for educators and curriculum developers who wish to implement effective and sustainable gamification strategies in ELT.